OPTIMIZATION OF DISTANCE EDUCATION IN THE APPLICATION CONTEXT OF VIRTUAL CLASSROOM TECHNOLOGY - DEMIANIUK, Antonina; BILOUS, Iryna (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2024)
Annotation. The importance of distance learning with an emphasis on its efficiency, effectiveness and impact on the educational process is explored in the article. The key aspects that contribute to the improvement of pedagogical methods and the introduction of technological innovations in distance education are discussed. Issues of availability, quality, and variety of educational opportunities in this form of education are highlighted separately. It is noted that distance learning differs from traditional in many aspects, in particular, flexibility in choosing the time and place of learning, the ability to combine learning with professional activity, and wide access to educational resources. Particular attention is paid to the information technology aspects of distance learning, such as multimedia capabilities, interactive tools, chats, forums, and the creation of virtual classrooms for collaborative work. The role of synchronous learning mode and virtual classes in ensuring real-time interaction between teachers and students is emphasized. Challenges of distance education, such as the ability of students to study independently, their motivation, communication, individualization of the process and identification of participants are considered in the article. The optimization of distance learning is defined as an important factor in the development of the modern education system, which contributes to increasing the accessibility and quality of education through the integration of information and communication technologies. The impact of the virtual educational environment on improving the quality of education is explored, where the emphasis is on creating interactivity, cooperation and knowledge exchange between participants in the educational process. The authors propose an algorithm for optimizing distance learning using virtual classroom technology, which includes participant needs analysis, content adaptation, technical support, and performance evaluation. The functionality of virtual classrooms, including video conferencing, interactive whiteboards, chat rooms, multimedia materials and tools for collaborative work, is being explored. Directions for improving the use of virtual classroom technology through the introduction of accessibility for people with disabilities and linguistic diversity, as well as the creation of "microclasses" for joint work on projects, are proposed. The importance of inclusiveness and interactivity in distance learning as a basis for creating an effective, flexible and progressive education system that meets modern requirements is emphasized in the article.